2014
DOI: 10.1007/s00268-014-2846-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymphovascular Invasion in Node‐Negative Gastric Cancer

Abstract: LVI could be an indicator of biological aggressiveness and may be a reliable prognostic factor for node-negative gastric cancer. LVI should be considered in postoperative management of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
4
39
0
Order By: Relevance
“…Nevertheless, the trend remained consistent after adjusting for poor prognostic factors such as lymphatic and/or blood vessel invasion (24)(25)(26), perineural invasion (27), stage and treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, the trend remained consistent after adjusting for poor prognostic factors such as lymphatic and/or blood vessel invasion (24)(25)(26), perineural invasion (27), stage and treatment.…”
Section: Discussionmentioning
confidence: 73%
“…In patients without lymph node metastases, lymph vascular invasion (LVI) should be finely investigated by pathologists, as LVI is a well-known risk factor for distant and nodal recurrences (14,15). Lee et al found LVI to be an indicator of biological aggressiveness and a reliable independent and prognostic factor in pT1-3 pN0 gastric cancer patients, with an impact similar to that of the N1 group (16). Coherently, LVI should be considered in the postoperative management of pN0 gastric cancer.…”
Section: Clinical Impact Of Detected Lymph Nodesmentioning
confidence: 99%
“…The incidence of LN MM is lower than 10% in patients with node negative EGC [20] but it is higher in histologically diffuse type tumors [21] . The presence of MM influenced DFS, although the OS analysis revealed no significant difference between MMpositive and MMnegative patients [19] . The reverse transcriptase polymerase chain reaction proved to be the most sensitive method in the detection of MM [22] .…”
Section: Ln Involvementmentioning
confidence: 87%
“…These results are potentially associated with the elimination of MM in negative LNs [25] . Based on these findings, LVI and MM should be considered in posto perative management of gastric cancer [19] .…”
Section: Ln Involvementmentioning
confidence: 91%
See 1 more Smart Citation